Building modern SaaS applications with C# and .NET : build, deploy, and maintain professional SaaS applications - Watt, Andy (Packt Publishing, 2023)
Embark on a tech-tastic adventure and build Software as a Service (SaaS) applications using the Microsoft tech stack Purchase of the print or Kindle book includes a free PDF eBook Key Features Understand the core concepts of Software as a Service and their importance in building modern applications Build a wide array of key elements for SaaS applications using practical examples Learn to test, deploy, upgrade, and maintain a SaaS application Book DescriptionThere are several concepts that must be mastered to deliver functional and efficient SaaS applications. This book is perfect for developers and teams with experience in traditional application development looking to switch to SaaS and deliver slick and modern applications. You‘ll start with a general overview of SaaS as a concept and learn with the help of an example throughout the book to bring life to the technical descriptions. You’ll use the Microsoft .NET tech stack for development and C# as the programming language to develop your desired SaaS application. Delivering SaaS requires a deep understanding of all layers in the application stack. As you progress, you’ll learn how to approach the database layer, the API, and the UI to confidently approach application development using the SaaS model. Additionally, you’ll explore how to test, deploy, maintain, and upgrade each component of the application. By the end of this book, you will be well equipped to approach all aspects of delivering software using the SaaS paradigm. What you will learn Explore SaaS and understand its importance in modern application development Discover multi-tenancy and its impact on design decisions for SaaS Build, test, and deploy a database, API, and UI for a SaaS application Approach authentication and authorization like a pro Scale a SaaS application Employ C# and .NET to build SaaS applications Who this book is for If you are a software developer with an interest in developing apps using the ‘SaaS’ paradigm, or a tech lead, scrum master, or a director and founder - this book will help you understand how to build a SaaS application. If you are a Java developer looking to start fresh with distributed systems, this book is for you. A basic understanding of Java, Spring/Spring Boot, and Web services will help you get the most out of this book.